[Cars Pulling Bus From Water at Landmannalaugar] - Streng, Evelyn Fiedler (1975)
Photograph of cars pulling a bus from water at Landmannalaugar. The white and light blue bus is partially submerged in grey water ahead of the foot of a mountain in the background. Brown, blue, and red cars are attached to the bus with a rope, pulling it out onto a rocky beach below. Groups of people stand off to the side, watching the bus being pulled.